Nutritional Profiling and Shelf-life Analysis of Developed Bar (International Journal of Scientific Research in Science and Technology, 2024)
Developing a nutritionally dense snack presents a significant challenge for consumers seeking healthier options. This study focuses on a specially crafted bar designed to meet the needs of consumers looking for both convenience and nutrition in their snacks. The bar is made up of two main components: carefully selected raw materials and a digestion mix containing concentrated sulfuric acid. Raw materials are sourced from reliable suppliers, and the bar is developed using cutting-edge laboratory facilities. This bar has the potential to be classified as a functional food, offering unique health benefits to consumers. The study's objective is to assess the nutritional composition and shelf life of the bar, ensuring its success in the market. The nutritional analysis of the bar reveals notable differences between Sample 1 and Sample 2. These differences indicate that Sample 1 may be appealing to those seeking a nutrient-rich snack, while Sample 2 may be more suitable for individuals looking for quick sources of energy.
Keywords: Nutrition; Snack; Bar; Functional food; Shelf-life